Anna Kazumi Stahl, “our” Transnational Writer - Lila Bujaldón de Esteves (Revista de Culturas y Literaturas Comparadas, 2015)
This article presents Anna Kazumi Stahl (1963) as an example of a transnational writer who has chosen Buenos Aires as her place of residence and Argentine Spanish as the language for her writing. The author has multiple origins and cultural contacts: North American, Japanese, German, Argentine. All of them underlie her novel Flores de un solo día (2002) [Flowers for a Single Day], which problematizes its protagonist’s search for identity. For Argentine literature, which has already a significant corpus of immigration texts, A. Kazumi Stahl brings an echo of the globalized world situation.